The analysis of Sudden Infant Death Syndrome in Poland - Anna Lewandowska; Anna Stokłosa; Tomasz Lewandowski; Barbara Laskowska (Kazimierz Wielki University, 2017)
Introduction: Sudden Infant Death Syndrome is defined in literature similarly as a sudden and unexpected death of an infant occurring during sleep and, at the same time, causes of which cannot be explained based on anamnesis, circumstances of death or comprehensive post-mortem examinations. Sudden Infant Death Syndrome is considered to be the most frequent cause of death among infants in the developed countries. Incidence of SIDS in the whole world ranges from about 0.1 to 6.0/1,000 live births. As much as 90% concerns deaths in the first year of life of a child, whereas 70% stands for deaths for which the cause remains unknown. In SIDS, about 90% of cases concern children under 1 year old and, in particular, at the age of between 2 and 4 months. The aim: The aim of the study was to present the most significant aspects of SIDS as well as description and analysis of risk factors for occurrence of sudden infant death syndrome based on statistical data. Materials and methods: For the purpose of the study, the secondary data analysis and desk research technique have been applied. The analysis is based on statistical data from the time period 2009-2014 released by the Central Statistical Office of Poland. Results: In 2009-2014, the highest number of deaths of infants and new-borns was reported in 2009 with the number being as high as 2,327. In the following years, the number of deaths of new-borns and infants systematically decreased. In 2010 it was 2,057 and in 2011 - 1,836, in 2012 - 1,791, in 2013 - 1,684, and in 2014 - 1,583. The highest number of deaths of boys was reported in 2009 - 1,298, while the number of deaths of girls in that year, although it was the highest in the analysed period, was lower - 1,029. Conclusions: cases of death were more frequent among boys rather than girls. The highest number of deaths was reported among infants under the age of one month and the number decreased with an increasing infants' age. More cases of death were reported in the city area rather than in a village.